DESCRIPTIVE PROFILE OF SHOULDER AND SCAPULAR ROM AND STRENGTH MEASUREMENTS IN JUNIOR RECREATIONAL AND ELITE GYMNASTS. Issue 7 (11th March 2014) - Cools, A; van De Lanotte, L
Abstract : Background: Gymnastic sports requires repetitive high load overhead movements that can lead to upper extremity injury. The scapula and the shoulder play a vital role in injury-free performance. Scapular dysfunction and glenohumeral changes in strength and range of motion (ROM) have been associated with shoulder injury in the overhead athlete. Objectives: The purpose of this study was to describe scapular position and strength, and shoulder ROM and strength variables in a population of junior and adolescent recreational and elite gymnastics in the age categories 6–18 years. Design: Descriptive study, cross-sectional design. Setting: Training sports facilities. Participants: Junior and adolescent gymnastics from different disciplines. Risk factor assessment: A clinical screening protocol, using a digital inclinometer and a hand held dynamometer, to measure strength and mobility of the shoulder girdle. Main outcome measures: (1) scapular upward rotation (UR) at several angles of arm elevation, (2) isometric scapular muscle strength (3) glenohumeral ROM, and (4) isometric rotator cuff strength. Results: Data will be collected sept-dec 2013, and will be presented at the conference. Conclusion: This study provides a descriptive profile of shoulder and scapular measurements in a population of elite and recreational gymnasts. These data may help the clinician to screen healthy gymnasts in their injury prevention program.